The implication of agency theory in micro-business financing of sharia cooperatives in Indonesia - Martiana, Andri; Kassim, Salina; Zakariyah, Habeebullah (Asian Scholars Network, 2023)
The study examines the application of agency theory to Baitul Maal wa Tamwil (BMT), an Indonesian Sharia Cooperative, in terms of asset growth and socioeconomic implications. The paper examines BMT's cooperative structure, which complicates the agency relationship and calls into question the responsibilities of agents and principals to the finance practises of BMTs in Indonesia. However, BMTs continue to encounter agency issues in their real-world situations. They can employ a variety of financing contracts, including Murabaha, Mudaraba Musharakah, and Qardh hasan, however some may have problems. According to the findings, the paradigm of thinking based on Islamic principles should be examined in the context of BMT. Further empirical research on agency difficulties at BMTs in Indonesia can be carried out with the approval of the Ministry of Cooperatives, SMEs, and Finance.